Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai di Pemerintah Kabupaten Mahakam Ulu - Kori Aprilia; Laura Lahindah (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The Golden Indonesia Vision 2045 demands to improve the quality of human resources in local governments. The performance of the Mahakam Ulu Regency Government shows a decline in 2024, indicating the issue of employee performance, even though rewards and punishments have been implemented. This quantitative research aims to analyze the partial and simultaneous influence of rewards and punishments on employee performance. A sample of 100 employee respondents in several OPDs in Mahakam Ulu Regency was taken by simple random sampling, with data collected through questionnaires and analyzed using multiple linear regression, preceded by a classical assumption test (normality, multicollinearity, heteroscedasticity). The results of the study show that the partial implementation of Reward and Punishment has a positive and significant effect on Employee Performance, respectively. Furthermore, simultaneously, Reward and Punishment also have a positive and significant effect on Employee Performance, able to explain 69.5% of performance variations. This research is expected to provide understanding and strategic recommendations to improve employee performance in a sustainable manner, supporting regional and national visions.